2020
DOI: 10.3390/su122310077
|View full text |Cite
|
Sign up to set email alerts
|

Green Purchase Behavior of University Students in Hungary: An Empirical Study

Abstract: In this modern age of digitalization, consumers have access to an ample amount of information regarding a product’s quality and benefits, which makes consumers more conscious of their consumption patterns and their impact on social and environmental development. Likewise, marketing strategies have also taken a dramatic leap forward and started focusing on social responsibility, ethics, and environmental protection. The notion of environmental sustainability has created a market niche over several decades and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 82 publications
7
79
0
5
Order By: Relevance
“…Previous studies have shown that consumers were motivated to purchase organic food due to health and environmental concerns [20,22,23]. Studies also found that consumers' health consciousness predicted their consumption of organic food [24][25][26]. Subjective norms including the influence of family and friends, compounded with lifestyle trends, also show a significant influence on the intention to purchase organic food [27,28].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that consumers were motivated to purchase organic food due to health and environmental concerns [20,22,23]. Studies also found that consumers' health consciousness predicted their consumption of organic food [24][25][26]. Subjective norms including the influence of family and friends, compounded with lifestyle trends, also show a significant influence on the intention to purchase organic food [27,28].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…As regards the domestic consumption of organic food, studies found that European consumers were driven by health consciousness, environmental concern, quality of life, and technological development [24,37]. Although environmental and health consequences can influence organic consumerism, the affordability of organic food was significant in determining consumers' food choices, particularly those in Italy and Hungary [25].…”
Section: Organic Food Consumption Trends In Hungary and Malaysiamentioning
confidence: 99%
“…Consumers who endorse biospheric values are concerned about the impact of their own consumption pattern, for example, in terms of greenhouse gas emissions [46]. Furthermore, environmental awareness of consumers is related to pro-environmental consumption choices, such as choosing products that are made of recycled constituents and reduce waste [21].…”
Section: Effect Of Consumers' Value Orientations On Sustainable Consumption Patternsmentioning
confidence: 99%
“…Consumers are believed to be more aware than ever before about how their consumption patterns may threaten the quality of the environment and sustainable development [21,47,48]. They are increasingly conscious about the potential devastating impact humanity has on the biosphere.…”
Section: The Moderating Role Of Worldviewsmentioning
confidence: 99%
See 1 more Smart Citation